2016
DOI: 10.1007/s10869-016-9456-7
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Evidence on Questionable Research Practices: The Good, the Bad, and the Ugly

Abstract: Purpose Questionable research or reporting practices (QRPs) contribute to a growing concern regarding the credibility of research in the organizational sciences and related fields. Such practices include design, analytic, or reporting practices that may introduce biased evidence, which can have harmful implications for evidence-based practice, theory development, and perceptions of the rigor of science. Design/Methodology/Approach To assess the extent to which QRPs are actually a concern, we conducted a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 69 publications
1
128
0
7
Order By: Relevance
“…In previous literature on QRP use, data fabrication is included as a questionable practice. Fabrication, along with falsification and plagiarism, have been previously labeled "FFP" and are not considered in this dissertation as they are not questionable but instead academically dishonest (Steneck, 2006 While there are some instances when QRP use may be justified, when they are used, they contribute to the false-positive rate observed in the published literature (Banks, Rogelberg, Woznyj, Landis, & Rupp, 2016;Fanelli, 2009). Not only does QRP use increase the number of false-positive findings (i.e.…”
Section: How Many Psychologists Use Questionable Research Practices? mentioning
confidence: 99%
“…In previous literature on QRP use, data fabrication is included as a questionable practice. Fabrication, along with falsification and plagiarism, have been previously labeled "FFP" and are not considered in this dissertation as they are not questionable but instead academically dishonest (Steneck, 2006 While there are some instances when QRP use may be justified, when they are used, they contribute to the false-positive rate observed in the published literature (Banks, Rogelberg, Woznyj, Landis, & Rupp, 2016;Fanelli, 2009). Not only does QRP use increase the number of false-positive findings (i.e.…”
Section: How Many Psychologists Use Questionable Research Practices? mentioning
confidence: 99%
“…In NHST, the tenability of a null hypothesis (i.e., no effect or relation) is primarily judged based on the observed p value associated with the test of the hypothesis, and values smaller than 0.05 are often judged as providing sufficient evidence to reject it (Bettis et al, 2016;Goldfarb & King, 2016). Of the many problems associated with this interpretation of p values, the most pernicious is that it motivates researchers to engage in a practice called ''p-hacking'' and to report ''crippled'' p values (see below) (Aguinis, Werner, Abbott, Angert, Park, & Kohlhausen, 2010;Banks, Rogelberg et al, 2016). For example, consider a researcher who interprets p = 0.0499 as sufficient evidence for rejecting the null hypothesis, and p = 0.0510 as evidence that the null hypothesis should be retained, and believes that journals are more likely to look favorably on rejected null hypotheses.…”
Section: Reporting Of P Valuesmentioning
confidence: 99%
“…Clearly, it is difficult to make the case that research results are credible and useful if they are irreproducible and not replicable. Unfortunately, there is a proliferation of evidence indicating that lack of reproducibility and replicability are quite pervasive (e.g., Banks, Rogelberg, Woznyj, Landis, & Rupp, 2016;Cortina, Green, Keeler, & Vandenberg, 2016;Cuervo-Cazurra et al, 2016;Ioannidis, 2005;Open Science Collaboration, 2015;Schwab & Starbuck, 2017). Accordingly, as noted by Verbeke, Von Glinow, and Luo, ''… the IB discipline faces the challenges of remaining at par with the methodological standards in adjacent fields for validity, reliability, replicability and generalizability'' (Verbeke et al, 2017: 6).…”
Section: Introductionmentioning
confidence: 99%
“…It amounted to academic dissembling even though I knew it was commonly done" (Anonymous, 2015: 214). Banks, Rogelberg, Woznyj, Landis and Rupp (2016) examined 64 business studies and inferred that 91% of these studies showed evidence of covert, undesirable practices in the conduct or reporting of research.…”
Section: Covert Research Practicesmentioning
confidence: 99%
“…These practices both distort evidence about the usefulness of theories and undermine confidence in the conclusions reported (as summarized in Table 1). The undesirable properties of these practices are wellestablished in the social sciences and the corresponding methods literature (Banks, Rogelberg, et al, 2016;Kepes, Bennett & McDaniel, 2014;Landis & Rogelberg, 2013;Schwab et al, 2011;Simmons et al 2011;Starbuck, 2016a).…”
Section: P-hacking and Best-model Reporting P-hacking (Or Data Mining)mentioning
confidence: 99%